2017
DOI: 10.1186/s12888-017-1225-2
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative process evaluation of a psycho-educational intervention targeted at people diagnosed with schizophrenia and their primary caregivers in Jordan

Abstract: BackgroundSchizophrenia is a serious form of mental illness that often requires long term care. Empirical findings indicate that combining a psycho-educational intervention (PEI) with neuroleptic medication to treat schizophrenia is effective. However, there is little information on the therapeutic mechanism of PEIs.MethodsA qualitative process evaluation was conducted with a purposive sample of people diagnosed with schizophrenia (PDwS, n = 8) and their Primary Caregivers (PCs, n = 9) who had received PEI as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 44 publications
0
36
0
1
Order By: Relevance
“…Identifying predictors of QOL will also help in developing new programmes that aim to improve the QOL of people with schizophrenia. Previous studies showed that people with schizophrenia had poor knowledge about their illness . Moreover, the healthcare system in Jordan focuses on a biomedical model of treatment for such patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying predictors of QOL will also help in developing new programmes that aim to improve the QOL of people with schizophrenia. Previous studies showed that people with schizophrenia had poor knowledge about their illness . Moreover, the healthcare system in Jordan focuses on a biomedical model of treatment for such patients.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that people with schizophrenia had poor knowledge about their illness. 42,45 Moreover, the health-…”
Section: Introductionmentioning
confidence: 99%
“…In total, 344 dyads of patients and their caregivers were recruited into the studies. The designs were two RCTs (36,37), two nonrandomized trials (38,39) and one qualitative study (40). See table 1 for the descriptive characteristics of the studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The interventions in the five studies were delivered in Egypt (3) and Jordan (2). The qualitative study (40) was a second stage from another study in the review (37). Despite the difference in the content, all the studies shared the component of psychoeducation, and two included communication and problem-solving skills (36,37), while ElShafei et al (2006) used counselling sessions.…”
Section: Intervention Characteristicsmentioning
confidence: 99%
“…In total, 344 dyads of patients and their caregivers were recruited into the studies. The designs were two RCTs (29,30), two non-randomized trials (31,32) and one qualitative study (33). See table 1 for the descriptive characteristics of studies.…”
Section: Study Characteristicsmentioning
confidence: 99%